2019
DOI: 10.1002/ijc.32574
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of tea and coffee intake and risk of glioma

Abstract: Tea and coffee have antioxidant and neuroprotective effects. Observational studies suggest that tea and coffee intake may reduce cancer risk, but data on glioma risk are inconclusive. We evaluated the association between tea, coffee and caffeine intake and glioma risk in the female Nurses' Health Study (NHS) and Nurses' Health Study II (NHSII) and the male Health Professionals Follow‐Up Study (HPFS). Cumulative intake was derived from validated quadrennial food frequency questionnaires. Glioma cases were confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Cumulative antioxidant capacity found in coffee is higher than that found in any given fruit and vegetable (7) . However, the benefit of coffee or tea consumption on the risk of glioma is still controversial; two most recent studies published in 2020 showed conflicting results, similar to previous studies (4,8) . In this systematic review and dose-response meta-analysis, we aimed to assess whether coffee and tea consumption is related to the risk of glioma by synthesising the latest evidence from cohort studies.…”
mentioning
confidence: 76%
“…Cumulative antioxidant capacity found in coffee is higher than that found in any given fruit and vegetable (7) . However, the benefit of coffee or tea consumption on the risk of glioma is still controversial; two most recent studies published in 2020 showed conflicting results, similar to previous studies (4,8) . In this systematic review and dose-response meta-analysis, we aimed to assess whether coffee and tea consumption is related to the risk of glioma by synthesising the latest evidence from cohort studies.…”
mentioning
confidence: 76%
“…Concerning skin, an organ often found as a target for AA-induced carcinogenesis in animal studies [ 36 , 37 ], meta-analyses indicate borderline protective effects of coffee consumption against melanoma [ 98 , 99 , 100 ] and basal cell skin cancers [ 101 , 102 , 103 ]. On a similar note, no association was found between coffee consumption and the risk of brain tumors [ 104 , 105 ] or gliomas [ 106 , 107 , 108 ], as reported in meta-analyses and reviews. Similarly, no association was found between coffee consumption and oral or pharyngeal cancer risk [ 109 , 110 ].…”
Section: Impact Of Coffee On Cancer Risk In Humansmentioning
confidence: 78%
“…In the case of coffee and tea consumption, no effect on glioma was observed, taking into account both the entire observation period and after excluding the first 5 years of follow-up [ 13 ]. In 2019, the combined data from the Nurses’ Health Study (I and II) and the Health Professionals Follow-Up Study (HPFS) were studied by Cote et al [ 21 ]. Consumption of tea and coffee was assessed based on the information provided in the validated food frequency questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…Though when the gender breakdown was included, the relationships were not confirmed. Moreover, a relevant inverse relationship was determined between tea consumption at the baseline and glioma risk in the pooled analysis ( p = 0.02) and in females ( p = 0.05) but not in males ( p = 0.22) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%